Influence of resistant starch on microstructure and physical properties of breaded fish fillets - Moradi, Yazdan; Bakar, Jamilah; Che Man, Yaakob; Syed Muhammad, Sharifah Kharidah (Iranian Fisheries Research Organization, 2014)
The influence of two types of resistant starches (RS2 and RS4) substituted at 10 and 20% in the batter formulation on the water retention capacity of the batter and on the texture, color, fat content and microstructure of the pre-fried and oven cooked breaded black pomfret fillets (Parastromateus niger) were studied. A significant (p<.05) increase of water retention capacity (3-7%) was found in all batters with RS as compared to the control, which was reflected in the moisture content of the breaded fillets. The addition of the resistant starches significantly (p<.05) decreased the fat content of the breaded fillets. Instrumental texture analysis showed that the presence of the RS in the batter also resulted in a significant increase in hardness and fracturability of the products. The L* and b* values of breading materials were increased in the samples containing 20% of RS.